Research on the Degree of Nominal and Real Convergence between the Member States of the European Monetary Union in the Period 1999-2000 - Kirova, Silvia (Research Papers, 2012)
The achievement of high degree of nominal and real convergence between the participating members is of key importance in the process of creation and enlargement of the European Monetary Union (EMU).The current research aims at studying with the sigma-convergence method the degree of nominal and real convergence between the seventeen member-states of the Euroarea and how it has changed in the period 1999-2010. The degree of nominal convergence is measured in terms of the Maastricht nominal convergence criteria. The degree of real convergence is assessed for GDP per capita and labor productivity.The results of the research are ambiguous. The EMU member-states have achieved convergence only in terms of inflation and income. As for the other parameters, there is no evidence of convergence.